Pengaruh Profitabilitas Dan Leverage Terhadap Tax Avoidance Dengan Sales Growth Sebagai Variabel Moderasi - Mohamad Iqbal; Ustadus Sholihin; Zulfia Rahmawati (Populer: Jurnal Penelitian Mahasiswa, 2023)
Companies must struggle to survive and be the best, this encourages companies to use various strategies and innovations to prevent bankruptcy in the laws of law there are gaps that can be utilized by taxpayers to reduce the tax burden that must be paid. One of them is tax avoidance. The purpose of this study is to determine the effect and explain profitability, leverage on tax avoidance with sales growth as moderation variables in consumer goods companies listed on the Indonesia Stock Exchange for 2020-2021. Types of research approaches are quantitative, with a population of 4 companies and 32 data samples The quarterly financial uses using purposive sampling for sample determination. Data analysis techniques conducted with descriptive statistical analysis, testing of panel data regression estimation models, classical assumption tests, multiple linear analysis, t-test, and moderation regression analysis. The results of this study were obtained that the partial profitability variable had a significant effect on tax avoidance and partially leverage had no significant effect on tax avoidance. The results of moderation regression analysis obtained by the results of sales growth instead of the moderation variable between profitability and leverage of tax avoidance.